2007
DOI: 10.1002/nur.20187
|View full text |Cite
|
Sign up to set email alerts
|

High‐density lipoprotein prevents organ damage in endotoxemia

Abstract: High-density lipoprotein (HDL) may decrease organ injury in sepsis. This study was designed using an animal model to mimic people who had a high HDL level and to test HDL effects on preventing organ damage in endotoxemia. Endotoxemia was induced by an infusion of lipopolysac-charide (LPS) after HDL or LDL administration. Levels of blood biochemical substances, nitrate/nitrite, and TNF-alpha in sera were measured. Pathological examinations were performed 72 hours after LPS infusion. HDL decreased the endotoxin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…ApoA-I knockout mice, which lack HDL, exhibit decreased LPS neutralization in the serum compared with serum from control mice (Guo et al 2013); overexpression of apoA-I moderately improves survival compared to controls, suggesting that HDL elevation may protect against septic death. In endotoxemic rats, in which LPS has been infused after HDL administration, HDLs attenuate LPS-induced organ damage accompanied by lower TNF-α and nitric oxide production (Lee et al 2007). In addition to its role in LPS neutralization, HDLs exert its protection against sepsis also by promoting LPS clearance; in fact, almost all LPS exists in the complex LPS-HDL in the blood (Ulevitch et al 1979(Ulevitch et al , 1981, the HDL receptor SR-BI binds and mediates LPS uptake, and HDLs promote SR-BI-mediated LPS uptake (Vishnyakova et al 2003).…”
Section: Interaction Of Hdl With Lps and Gram-negative Bacteriamentioning
confidence: 99%
“…ApoA-I knockout mice, which lack HDL, exhibit decreased LPS neutralization in the serum compared with serum from control mice (Guo et al 2013); overexpression of apoA-I moderately improves survival compared to controls, suggesting that HDL elevation may protect against septic death. In endotoxemic rats, in which LPS has been infused after HDL administration, HDLs attenuate LPS-induced organ damage accompanied by lower TNF-α and nitric oxide production (Lee et al 2007). In addition to its role in LPS neutralization, HDLs exert its protection against sepsis also by promoting LPS clearance; in fact, almost all LPS exists in the complex LPS-HDL in the blood (Ulevitch et al 1979(Ulevitch et al , 1981, the HDL receptor SR-BI binds and mediates LPS uptake, and HDLs promote SR-BI-mediated LPS uptake (Vishnyakova et al 2003).…”
Section: Interaction Of Hdl With Lps and Gram-negative Bacteriamentioning
confidence: 99%
“…This seminal discovery has been validated in humans at risk of developing metabolic disease such as those feeding on a fat‐enriched diet . The absorption of LPS is facilitated by chylomicrons and it circulates in the blood linked to several LPS binding proteins and also with lipoproteins (figure ) , reflecting the tight link of LPS biology to lipid metabolism. Numerous subsequent studies have demonstrated the importance of the LPS pathway to the onset of metabolic diseases .…”
Section: Molecular Hypotheses Of the Host‐microbiota Crosstalkmentioning
confidence: 99%
“…Pretreatment with rHDL was shown to have a significant effect in inhibiting endotoxin-induced organ damage, such as the lowered neutrophil infiltration in lung seen in histological examination (23,24). Hubsch, Casas, and Doran (25) found that both prophylactic and therapeutic rHDL administration could improve clinical outcome, with a significant attenuation of acidosis in the rabbit Gram-negative bacteremia model.…”
Section: Histological Sections Of Lung Tissuementioning
confidence: 99%